An Architectural Model for the 21st Century School: Synthesis of Research Results - Vilbikienė, Grėtė (Acta Paedagogica Vilnensia, 2021)
This paper is intended to identify the most relevant and most frequently discussed research topics in the literature, including pedagogy and the physical learning environment. It can be stated that the goals and objectives of education may even indirectly be related to the physical learning environment; therefore, it is relevant to analyze the ways, means, aspects and methodologies of this interface in the research works of other researchers. To achieve this goal, the article presents a systematic analysis of literature sources. Based on the conclusions of the systematic analysis and the goals and objectives of modern education, the model of a good school in the general case was formed and presented in the article. This is the 21st century school model that reveals those factors and characteristics of the physical learning environment that would help create a physical learning environment corresponding to modern education.